RAB40C gene polymorphisms rs62030917 and rs2269556 are associated with an increased risk of lumbar disc herniation development in the Chinese Han population. (17th March 2021) - Liu, Kexun; Huo, Hongjun; Jia, Wenchao; Li, Manglai; Xiong, Zichao; Sun, Yao; Wu, Jiamin; Li, Haiyue; Liu, Jianfeng; Liu, Yuanwei; Jin, Tianbo; Li, Bin; et al.
Abstract: Background: Lumbar disc herniation (LDH) places a serious burden on the daily lives and socioeconomics of people. Although the pathogenesis of LDH is complex, genetic factors such as single nucleotide polymorphisms (SNPs) may affect the risk of developing LDH. In the present study, we aimed to elucidate the effect of RAB40C SNPs on the risk of LDH in the Chinese Han population. Methods: We investigated 508 LDH cases and 508 healthy controls for this case–control study. Three tag SNPs in RAB40C were selected and genotyped using the Agena MassARRAY platform (Agena Bioscience, San Diego, CA, USA). After adjusting for age and gender, odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using unconditional logistic regression. Results: In the allele model, we found rs62030917 and rs2269556 in RAB40C with a minor G allele significantly increased the risk of LDH (rs62030917: OR = 1.23, 95% CI = 1.00–1.50, p = 0.046; rs2269556: OR = 1.21, 95% CI = 1.02–1.45, p = 0.033). In genetic model analysis, rs2269556 was associated with an increased risk of LDH under both codominant (OR = 1.49, 95% CI = 1.03–2.15, p = 0.035) and log‐additive models (OR = 1.21, 95% CI = 1.01–1.45, p = 0.035). rs62030917 of RAB40C was associated with an increased risk of LDH under codominant, recessive and log‐additive models ( p < 0.05) only among individuals younger than 49 years after stratification by age. Conclusions: For the first time, our results suggest that rs62030917 and rs2269556 in the RAB40C gene influence genetic susceptibility to LDH. Abstract : In the 508 LDH cases and 508 healthy controls, the Agena MassARRAY platform was used to genotype rs4984677, rs62030917 and rs2269556 in the RAB40C gene and use unconditional logistic regression for calculation. Our results indicate that rs62030917 and rs2269556 in the RAB40C gene influence genetic susceptibility to LDH.